Aversion to light is associated with impulsivity - Lander, Alicia C.; Phillips, Andrew J. K.; McGlashan, Elise M.; Cain, Sean W. (Frontiers in Psychology, 2024)
Exposure to bright light can be visually aversive. This study explored the association between light aversion and various facets of impulsivity. A total of 1,245 participants completed the UPPS-Impulsive Behaviour Scale to assess five facets of impulsivity. Additionally, participants responded to questions regarding their aversion to light (e.g., how aversive do you find bright light?). Spearman's correlation coefficients (rho) revealed that individuals who find light physically aversive, or who experience a negative physical response to exposure (e.g., nausea or headache) triggered by bright indoor light or sunlight, tend to act impulsively under extreme negative and positive affect. Individuals who experience a negative physical response to exposure display greater premeditation, indicating a higher likelihood of considering the potential consequences of their actions. Moreover, these individuals score lower on sensation-seeking, suggesting a reduced inclination to seek out thrilling or novel experiences.These results reveal a complex relationship between light aversion and impulsivity, where those who find light aversive tend to be less impulsive in general, but more impulsive under extreme positive or negative affect.